2022
DOI: 10.3389/fnut.2022.927092
|View full text |Cite
|
Sign up to set email alerts
|

Biological Actions, Implications, and Cautions of Statins Therapy in COVID-19

Abstract: The Coronavirus Disease 2019 (COVID-19) showed worse prognosis and higher mortality in individuals with obesity. Dyslipidemia is a major link between obesity and COVID-19 severity. Statins as the most common lipid regulating drugs have shown favorable effects in various pathophysiological states. Importantly, accumulating observational studies have suggested that statin use is associated with reduced risk of progressing to severe illness and in-hospital death in COVID-19 patients. Possible explanations underli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…4,28 These supposed protective effects of statins were attributed to: reducing cholesterol, inhibition of viral entry and replication, anti-inflammatory and immunomodulatory, as well antithrombotic and antioxidant. 27,28 However, the results of most RCTs and this meta-analysis failed to demonstrate these benefits. The vast majority of meta-analyses of statins for COVID-19 included primarily observational studies and reached similar conclusions that statins reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,28 These supposed protective effects of statins were attributed to: reducing cholesterol, inhibition of viral entry and replication, anti-inflammatory and immunomodulatory, as well antithrombotic and antioxidant. 27,28 However, the results of most RCTs and this meta-analysis failed to demonstrate these benefits. The vast majority of meta-analyses of statins for COVID-19 included primarily observational studies and reached similar conclusions that statins reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown that statins use is associated with a reduced risk of disease progression and in-hospital death in patients with COVID-19. 4,28 These supposed protective effects of statins were attributed to: reducing cholesterol, inhibition of viral entry and replication, anti-inflammatory and immunomodulatory, as well antithrombotic and antioxidant. 27,28 However, the results of most RCTs and this meta-analysis failed to demonstrate these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been considered as a potentially beneficial drug class in COVID-19 patients, since pre-hospital statin use has been associated with reduced inflammatory responses, as evident by lower levels of CRP and IL-6 14 . It has been proposed that statins might significantly reduce the attachment and internalization of SARS-CoV-2 by lowering membrane cholesterol levels 14 , 15 . In addition, statins exert antithrombotic and antioxidative properties, which could be of clinical importance in COVID-19 patients, who present a pro-thrombotic state 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that statins might significantly reduce the attachment and internalization of SARS-CoV-2 by lowering membrane cholesterol levels 14 , 15 . In addition, statins exert antithrombotic and antioxidative properties, which could be of clinical importance in COVID-19 patients, who present a pro-thrombotic state 15 . Other hypolipidemic treatments, such as fibrates and niacin, have been tested in clinical trials as potential therapeutic interventions in patients with COVID-19, with limited results 16 .…”
Section: Discussionmentioning
confidence: 99%
“…11 By doing so, statins help lower cholesterol levels, prevent coronavirus infection, and attenuate COVID-19-related inflammation. 124 Statins such as atorvastatin (19, Figure 5), lovastatin (20, Figure 5), and simvastatin (21, Figure 5) can also prevent COVID-19-related cardiovascular complications, 125,126 Figure 5. However, statins have also been shown to enhance ACE2 expression in the heart of experimental models, 127 raising safety concerns regarding their use in patients with COVID-19.…”
Section: Lipid-inspired Therapeutics For Covid-19mentioning
confidence: 99%